2002
DOI: 10.1063/1.1446849
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Coulomb explosion and kinetic energy release in clusters of heterocyclic compounds

Abstract: The studies presented herein elucidate details of the Coulomb explosion event initiated through the interaction of heterocyclic clusters with an intense femtosecond laser beam (⩾1 PW/cm2). Clusters studied include 7-azaindole and pyridine. Covariance analysis verifies that the fragmentation channels are competitive. Kinetic-energy analyses, from experiment and simulation, suggest that Coulomb exploded fragments are created with varying amounts of energy and have a strong mass-to-charge relationship. Backward-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…This can be accomplished either by a marked enhancement of the repulsive Coulomb energy or by the dramatic reduction of the cohesive surface energy. The increase of E(Coulomb) was experimentally attained for cluster Coulomb explosion induced by ultrashort (1-10 fs) multielectron ionization and nuclear dynamics (10-100 fs) of molecular clusters, e.g., ) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(37)(38)(39)(40). Femtosecond electron dynamics, involving inner and outer cluster ionization (29), strips the cluster atoms͞molecules of their outer shell valence electrons, producing highly charged clusters on a time scale shorter than nuclear motion.…”
Section: Epiloguementioning
confidence: 99%
See 2 more Smart Citations
“…This can be accomplished either by a marked enhancement of the repulsive Coulomb energy or by the dramatic reduction of the cohesive surface energy. The increase of E(Coulomb) was experimentally attained for cluster Coulomb explosion induced by ultrashort (1-10 fs) multielectron ionization and nuclear dynamics (10-100 fs) of molecular clusters, e.g., ) (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(37)(38)(39)(40). Femtosecond electron dynamics, involving inner and outer cluster ionization (29), strips the cluster atoms͞molecules of their outer shell valence electrons, producing highly charged clusters on a time scale shorter than nuclear motion.…”
Section: Epiloguementioning
confidence: 99%
“…What are the fragmentation channels and under what conditions are they realized? What is the interplay between fission, i.e., instability toward dissociation, of the finite system into two (or a small number of) fragments and Coulomb explosion (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) into a large number ϳn (where n is the number of constituents) of ionic species? On the basis of molecular dynamics simulations of the fragmentation patterns of heavily charged Morse clusters we established that the Rayleigh instability limit (30) separates between nearly binary (or tertiary) spatially unisotropic fission and spatially isotropic Coulomb explosion into a large number of ionic fragments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The competing processes of evaporation and fission have been described by various liquid-drop models for clusters as diverse as atomic nuclei [42], multiply charged metal clusters [5,6], and highly charged solvent droplets [2,3]. The recent development of femtosecond lasers capable of rapidly ionizing many molecules in atomic or molecular clusters has permitted access to another dissociation process whereby a cluster undergoes a coulombic explosion, resulting in the isotropic ejection of many charged fragments [12][13][14][15].General characteristics of cluster dissociation are well illustrated by multiply charged metal clusters. Evidence for their dissociation was first observed by Sattler et al who, by measuring the mass and charge of Pb, Xe, and NaI clusters, observed half-integer cluster numbers that were interpreted to be doubly charged clusters [4].…”
mentioning
confidence: 99%
“…One motivation behind cluster research is that the transitional characteristics between bulk and molecular properties can be discovered by studying intermediate states of matter. Investigators have explored a wide variety of materials, including charged droplets of various liquids [2,3], clusters of noble metals [4][5][6][7][8], metal-ligand clusters [1,[9][10][11], highly charged clusters of noble gasses [12,13], small molecules [14,15], and ultracold clusters of transition metals [16]. Recently, investigators have formed noncovalently bound clusters of biologically important molecules, including clusters of amino acids and small peptides [17][18][19][20][21][22][23][24][25][26][27][28], and have studied their dissociation processes [18,20,[26][27][28].…”
mentioning
confidence: 99%